2015
DOI: 10.1039/c5cp00006h
|View full text |Cite
|
Sign up to set email alerts
|

Cluster evolution during the early stages of heating explosives and its relationship to sensitivity: a comparative study of TATB, β-HMX and PETN by molecular reactive force field simulations

Abstract: Clustering is experimentally and theoretically verified during the complicated processes involved in heating high explosives, and has been thought to influence their detonation properties. However, a detailed description of the clustering that occurs has not been fully elucidated. We used molecular dynamic simulations with an improved reactive force field, ReaxFF_lg, to carry out a comparative study of cluster evolution during the early stages of heating for three representative explosives: 1,3,5-triamino-2,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
(69 reference statements)
8
55
0
Order By: Relevance
“…Authors of the works 32,33,41,42 assert that the aggregation of carbon occurs already in the reaction zone. V. F. Anisichkin obtained in work 41 that carbon components of molecules of fine-grained mixture HEs completely mix before the oxidation, i.e., inside the reaction zone, and the oxidation occurs later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors of the works 32,33,41,42 assert that the aggregation of carbon occurs already in the reaction zone. V. F. Anisichkin obtained in work 41 that carbon components of molecules of fine-grained mixture HEs completely mix before the oxidation, i.e., inside the reaction zone, and the oxidation occurs later.…”
Section: Discussionmentioning
confidence: 99%
“…Breusov demonstrated from energy considerations 32 that the formation of carbon clusters is related to the partial breakup of chemical bonds in molecules and to the formation and growth of carbon skeleton. In the work, 33 the clustering of carbon at the heating of molecules of TATB, HMX and PETN was simulated by the molecular dynamics. Carbon nanostructures in the reaction zone were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular origin of the anisotropic sensitivity was suggested to be the intermolecular steric arrangements across a slip plane induced by shock compression. Wen et al [44] applied ReaxFF-MD to study cluster evolution during the early state of heating of explosives and its relationship to sensitivity. It was observed that clustering tendencies for explosives like β-HMX, TATB and PETN became less pronounced when the oxygen balance was increased.…”
Section: Introductionmentioning
confidence: 99%